ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI NIAT PERILAKU PENGGUNA E-WALLET PADA GENERASI Z DI KOTA SEMARANG MENGGUNAKAN KERANGKA UTAUT 2 - Audita, Laras; Meiranto, Wahyu (Diponegoro Journal of Accounting, 2024)
This research was conducted with the aim of analyzing factors that influence the behavioral intentions of e-wallet users in Semarang City. This research uses the Unified Theory of Acceptance and Use of Technology (UTAUT) 2 framework introduced by Venkatesh et al. (2012). There are eight factors that form the UTAUT 2 framework, namely performance expectations, business expectations, social influence, facilitating conditions, habits, price values, hedonic motivation, and behavioral intentions of technology users, in this case e-wallet. This research population includes all active e-wallet users in Indonesia with a research sample of 310 people in Semarang City who are included in Generation Z. Data collection was carried out through an online survey using social media. A total of 31 question items were analyzed using the PLS-SEM method with the help of SmartPLS 3 software. The research results show that the four hypotheses in this study are accepted. Social influence, habits, price value, and hedonic motivation have a significant positive effect on the behavioral intentions of e-wallet users. However, performance expectations, effort expectations, and facilitating conditions have no effect on e-wallet users' behavioral intentions. Furthermore, it is known that hedonic motivation is the factor that has the strongest influence compared to other UTAUT 2 factors in increasing behavioral intentions to adopt e-wallets.